Objective tests in economics (London: The English Language Book Society, 1979)
this book contain ten objective question test papers each consisting of forty questions. It is intended for students revising for G.C.E. "A" level, National Certificate/ Diploma, Higher National certificate/ diploma, Higher National Certificate/ Diploma and first professional examination in Economics.
Keywords: Economics